Pengaruh Pemasaran Jasa Pendidikan terhadap Brand Image di SDN 006 Teluk Pandan - Muhammad Zidan Maulana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study looks as how much the community's perceptions of SDN 006 Teluk Pandan's school image are impacted by educational service advertising tactics. Purposive sampling was utilized to gather data from parents of kids utilizing a quantitative method and basic linear regression analysis. With a F value of 175.239 and a significance level of 0.000 at the 95% confidence level, the results of the ANOVA test demonstrated a significant relationship between the school's brand image and the education promotion variable. According to regression research, school marketing tactics were 53.6% responsible for the public's favorable perception of the institution. With a correlation rating of 73.2%, the correlation results also showed a strong association between the two variables, indicating that the public's perception of the institution improves with more successful marketing campaigns. However, 46.4% of other factors—such as the caliber of professors, students' academic performance, facilities, administrative services, and the reputation of the educational institution—also affect the school's image but were not the subject of this study.